Melon breeding for disease resistance in the Republic of Uzbekistan - R. A. Khakimov; M. U. Khalimova (Овощи России)
Melon (Cucumis melo L.) is the most spread melon crop in Uzbekistan. More than 130 local varieties of melon are cultivated in various regions of the republic. Every year melons and gourds are cultivated on the area of 150 thousand hectares. The most harmful diseases of the melon are powdery mildew and Fusarium wilt. All local varieties of melon are susceptible to these diseases. Annually from these diseases, the yield of melon is reduced by 20-25%. The most effective way to combat these diseases is to develop resistant varieties. The Research Institute of Vegetable, Melon Crops and Potato has carried out long-term selection work to create melon varieties resistant to powdery mildew and Fusarium wilt. Breeding local varieties of melon with economically valuable traits and high test quality with genes for resistance to these diseases have been created and included in the State Register of Uzbekistan.